(untitled) (Ingenio Magno, 2018)
With the aim of knowing in detail the model maturity in management projects, The Organizational Project Management Maturity Model (Model OPM3), defined by the Project Management Institute (PMI), carried out a revision of existing Literature in different electronic data bases from scientific character and in publications recognized by the academic community. Model OPM3 allows to evaluate the present situation in the companies with respect to the propose practices by PMI in management of projects, management of programs and management of portfolios, being facilitated the corrective decision making and that entails to the success of the projects. The result of this exploratory investigation tries to describe the necessary elements for the application of a valuation, as well as elements of reference on applications of the same, in similar or diverse scopes cultural that can enrich, thanks to learned lessons, the implementation of the model, or is by means of an investigation or an application in the industry.